Histone H3 phosphorylation near the nucleosome dyad alters chromatin structure - North, Justin A. (Oxford University Press, 2014)
Nucleosomes contain ∼146 bp of DNA wrapped around a histone protein octamer that controls DNA accessibility to transcription and repair complexes. Posttranslational modification (PTM) of histone proteins regulates nucleosome function. To date, only modest changes in nucleosome structure have been directly attributed to histone PTMs. Histone residue H3(T118) is located near the nucleosome dyad and can be phosphorylated. This PTM destabilizes nucleosomes and is implicated in the regulation of transcription and repair. Here, we report gel electrophoretic mobility, sucrose gradient sedimentation, thermal disassembly, micrococcal nuclease digestion and atomic force microscopy measurements of two DNA–histone complexes that are structurally distinct from nucleosomes. We find that H3(T118ph) facilitates the formation of a nucleosome duplex with two DNA molecules wrapped around two histone octamers, and an altosome complex that contains one DNA molecule wrapped around two histone octamers. The nucleosome duplex complex forms within short ∼150 bp DNA molecules, whereas altosomes require at least ∼250 bp of DNA and form repeatedly along 3000 bp DNA molecules. These results are the first report of a histone PTM significantly altering the nucleosome structure.